Time-of-day variability and circadian rhythms of groß and fine motor skills in patients with acquired brain damage - Endress, C; Jasper, I; Häußler, A; Hermsdörfer, J (Klinische Neurophysiologie, 2010)
Introduction: Human skills such as e.g. groß and fine motor skills are influenced by circadian rhythms. During acute therapy and rehabilitation patients with brain damage are faced with massive changes of their daily life routines. Beyond it seems conceivable that brain damage disturbs complex neurotransmitter systems and other neuronal processes that base on the function of the suprachiasmatic nucleus (SCN) controlling the endogenous clock. This study examines patients versus a matched controll group and attempts to identify alterations of groß and fine motor skills depending on the time-of-day and the environment (rehabilitation ward compared with daily life at home). Methods: 14 patients with stroke and other acquired brain damage (mean age 63.4 years) were tested. The patients executed different sensorimotor tasks in the morning and in the evening on a therapy day and a day at the weekend. They passed a psychomotor vigilance test (PVT) estimating reaction time and their ability to concentrate. Gross motor skills were assessed with maximum grip force using the Jamar hand dynamometer. The task for fine motor skills required subjects to follow a target force given on the screen by adjusting grip force against a force sensor. Data were registered for both hands in order to detect differences between the contralesional impaired hand and the ipsilesional hand. The control group (n=13, mean age 62.2 years) performed measurements in the morning and in the evening on a day of the weekend. Results: Patients' groß motor abilities showed stronger grip strength on the weekend (p<0.10) but there was no significant alteration between morning and evening measurement. The results of the fine motor task demonstrated a significant better performance in the evening (p<0.05) and also reaction time in the psychomotor vigilance test decreased in the evening. Discrepancy between therapy day and weekend was not statistically significant. Investigating the control group there was a significant increase of the maximum grip force in the evening hours (p<0.05) whereas fine motor skills yielded no obvious influence of circadian rhythms. Conclusion: The improvement of patients' fine motor skills as well as the shortening of reaction times in the vigilance task in the evening hours suggests that complex tasks underlie circadian rhythms in the patient. In particularly, pronounced deficits in the morning could be explained by a phenomenon called sleep inertia indicating a period of sensorimotor and cognitive decrements in the first hours after getting up. Time-of-day variability may have been enhanced as consequence of the brain damage because these effects were absent or weaker in the control group. The findings of this study suggest that therapy of fine motor skills during the second half of the day may lead to better training results and, as a consequence, to a higher motivation. Founded by the Gottlieb Daimler- and Karl Benz-Stiftung.